KRITIK MOESLIM ABDURRAHMAN TERHADAP BUDAYA KONSUMERISME KElAS MENENGAH - Joko Arizal (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2016)
This article explains Moeslim Abdurrahman’s view on the Indonesian Muslim middle class. The emergence of Muslim middle class in Indonesia was helped by New Order regime’s success in implementation of economic development and modernization. Their political attitude is mostly apolitical, their Islam is more culturally oriented, and they are a part of an increasingly consumerist society. It reveals that the combination between consumerism and religious attitude in this class creates a new type of pious social class. The research discusses the new middle class daily life style signified by the glamorous, trendyness, and prestigeousness of religious symbols and attributes. Their religious appearance and attitude show the shifting meaning of religion from the substantial to the material. The form of their religious life actually reduces the true meaning of Islam which promotes equality and social justice. The religious attitude of the new middle class Muslim has been losing its critical and emancipative function.